Pemberdayaan Berbasis Lingkungan Hidup di Desa Kabuaran Lumajang: Pengolahan Sampah Anorganik - Basuki, Basuki; Claudie Virginia Aracely; Salma Ardhli Tufa; Sri Wahyuni; Sholiha Nabita; Mohammad Rizal Romadhon (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Kabuaran Village in Lumajang faces challenges related to suboptimal inorganic waste management. Waste is often burned, resulting in air pollution. Through a community service program, the initiative aims to empower residents in processing inorganic waste. The activity began with observation, problem identification, and the discovery of low public awareness regarding the utilization of inorganic waste. To increase awareness and utilization of inorganic waste, the proponent held various activities, starting with socialization or counseling, followed by training in making handicrafts from recycled materials and techniques for marketing these products. This activity aims to meet sustainable development goals (SDGs) 12 and 13 related to consumption, production, and climate change. The results of the activity showed an increase in community understanding and skills in processing inorganic waste into economically valuable craft products. The community was also motivated to reduce waste burning and switch to recycling. This activity is expected to be sustainable and become an example for other villages in managing waste more responsibly.